3D Biomimetic Porous Titanium (Ti6Al4V ELI) Scaffolds for Large Bone Critical Defect Reconstruction: An Experimental Study in Sheep - Crovace, Alberto Maria; Lacitignola, Luca; Monopoli Forleo, Donato; Staffieri, Francesco; Francioso, Edda; Di Meo, Antonio; Becerra-Ratia, José; Crovace, Antonio; Santos-Ruiz, Leonor (MDPI, 2020)
The main goal in the treatment of large bone defects is to guarantee a rapid loading of the affected limb. In this paper, the authors proposed a new reconstructive technique that proved to be suitable to reach this purpose through the use of a custom-made biomimetic porous titanium scaffold. An in vivo study was undertaken where a complete critical defect was experimentally created in the diaphysis of the right tibia of twelve sheep and replaced with a five-centimeter porous scaffold of electron beam melting (EBM)-sintered titanium alloy (EBM group n = 6) or a porous hydroxyapatite scaffold (CONTROL group, n = 6). After surgery, the sheep were allowed to move freely in the barns. The outcome was monitored for up to 12 months by periodical X-ray and clinical examination. All animals in the CONTROL group were euthanized for humane reasons within the first month after surgery due to the onset of plate bending due to mechanical overload. Nine months after surgery, X-ray imaging showed the complete integration of the titanium implant in the tibia diaphysis and remodeling of the periosteal callus, with a well-defined cortical bone. At 12 months, sheep were euthanized, and the tibia were harvested and subjected to histological analysis. This showed bone tissue formations with bone trabeculae bridging titanium trabeculae, evidencing an optimal tissue-metal interaction. Our results show that EBM-sintered titanium devices, if used to repair critical bone defects in a large animal model, can guarantee immediate body weight-bearing, a rapid functional recovery, and a good osseointegration. The porous hydroxyapatite scaffolds proved to be not suitable in this model of large bone defect due to their known poor mechanical properties.
Keywords: Fracturas; Huesos; Titanio - Aleaciones; Implantes artificiales; Biomecánica; Ovejas de laboratorio; Traumatología veterinaria; Bone; Bone fracture; Bone repair; Metal endo-implant; Titanium alloy; Additive manufacturing; EBM (Electron Beam Melting); Biomechanics; Critical-size bone defects; Sheep animal model; Traumatology